Distale Radiusfraktur: Diagnostik und Therapie beim Erwachsenen = Distal radius fracture of the adult : diagnostics and therapy - Unglaub, Frank; Langer, Martin Franz; Hohendorff, Bernd; Müller, Lars Peter; Unglaub, Julia Marie; Hahn, Peter; Krimmer, Hermann; Spies, Christian (Der Orthopäde, 2017)
Fractures of the distal radius are very common. The majority of patients are elderly females. High impact trauma are often responsible for fractures in young men. Clinical and radiological diagnostics, including computer-assisted tomography (CAT) scan, are generally sufficient. The indication for conservative treatment is still recommended for specific fracture patterns. Application of palmar locking plates after open reduction proved to be efficacious for the majority of fracture patterns. Furthermore, precise detection and treatment of concomitant lesions are mandatory in order to prevent complications.